A Note on the q-Euler Numbers and Polynomials with Weak Weight α. (11th September 2011) - Lee, H. Y.; Jung, N. S.; Ryoo, C. S.
Abstract : We construct a new type ofq -Euler numbers and polynomials with weak weightα :E n, q ( α ), E n, q ( α ) ( x ), respectively. Some interesting results and relationships are obtained. Also, we observe the behavior of roots of theq -Euler numbersE n, q ( α ) and polynomialsE n, q ( α ) ( x ) with weak weightα . By means of numerical experiments, we demonstrate a remarkably regular structure of the complex roots ofq -Euler polynomialsE n, q ( α ) with weak weightα .